Asset Encumbrance, Bank Funding, and Fragility. (22nd September 2018) - Ahnert, Toni; Anand, Kartik; Gai, Prasanna; Chapman, James
Abstract: We model asset encumbrance by banks subject to rollover risk and study the consequences for fragility, funding costs, and prudential regulation. A bank's privately optimal encumbrance choice balances the benefit of expanding profitable, yet illiquid, investment funded by cheap long-term senior secured debt, against the cost of greater fragility from runs on unsecured debt. We derive testable implications about encumbrance ratios. The introduction of deposit insurance or wholesale funding guarantees induces excessive encumbrance and fragility. Limits on asset encumbrance or Pigovian taxes eliminate such risk-shifting incentives. Our results shed light on prudential policies currently being pursued in several jurisdictions. Received September 9, 2017; editorial decision July 28, 2018 by Editor Philip Strahan.